Congratulations by H.E. D. Davaa, Ambassador Extraordinary and Plenipotentiary of Mongolia to the Russian Federation, at the opening session. The international round table “Trade and economic cooperation between Mongolia and Russia. To the 100th anniversary of the establishment of diplomatic relations between Mongolia and Russia» - H.E. D. Davaa (Informaciâ i Innovacii)
.